Nickel (Ni2+) removal from water using gellan gum–sand mixture as a filter material - Tran, Thi Phuong An; Cho, Hoon; Cho, Gye Chun; Han, Jong In; Chang, Ilhan (Applied Sciences (Switzerland), 2021)
Microbial biopolymers have been introduced as materials for soil treatment and ground improvement purposes because of their ability to enhance soil strength enhancement and to reduce hydraulic conductivity. Several studies in the field of environmental engineering have reported heavy metal adsorption and removal from contaminated water using common biopolymers. In particular, gellan gum biopolymers have drawn significant attention for use in metal ion adsorption. This study aims to investigate the heavy metal adsorption capacity of a gellan gum biopolymer–sand mixture when nickel-contaminated water is pumped upward through a uniform gellan gum–sand mixture column. The main aims of this study are (1) to clarify the Ni2+ adsorption phenomenon of gellan gum-treated sand, (2) to assess the Ni2+ adsorbability of gellan gum–sand mixtures with different gellan gum content, and (3) to examine the gellan gum–sand filter thickness and flow rate effects on Ni2+ adsorption. The results of this experiment demonstrate the effectiveness of gellan gum in terms of Ni2+ adsorption and water flow rate control, which are essential criteria of a filter material for contaminated water treatment.
Keywords: Gellan gum; Hydraulic conductivity; Metal ion adsorption; Pore-clogging; Water absorption